Caracterização numérica unidimensional do fenômeno da detonação com validação experimental para diferentes teores de etanol na gasolina em um motor monocilíndrico de pesquisa - Thiago Dale Borgatti (2017)
Since the development of the first internal combustion engine, the knock phenomenon has always been a limiting factor for increasing efficiency. Therefore, along the years some alternatives to solve this problem have been developed, such as CFD (Computational Fluid Dynamics). This work presents the development of a numerical methodology for the elaboration and validation of a model that represents the Single Cylinder Research Engine - SCRE domain, of AVL® Company, in the Center of Technology Mobility - CTM-UFMG. The geometrical data from the engine, initial and boundary conditions were acquired in dynamometric tests, provided by CTM-UFMG experimental team. These data were used to build a model capable of reproducing heat transfer, burn rate, friction, and volumetric efficiency related phenomena, and this model showed a good correlation with experimental data using GT-Suite® software. Then, some experimental cases at the MBT and knock condition were reproduced and could be validated and used to evaluate the knock model sensibility available in the software. Besides the combustion and knock validation, a predictive combustion model was calibrated to numerically induce the knock in experimental cases acquired only at MBT. In this way, the predictive combustion model developed has proved to be a valuable tool capable to explore numerical conditions that are not easy to be reproduced experimentally due to the limits encountered by the structural capacity of an actual engine